Citizens' trade-offs in state merger decisions: Evidence from a randomized survey experiment - Sebastian Blesse; Friedrich Heinemann (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
Voters dealing with jurisdictional merger decisions face a trade-off between economies of scale and preference costs. Larger jurisdictions may offer cost advantages, yet the downside is that policies in larger units may be less aligned to voter preferences. Our study is the first to provide evidence on this trade-off on the individual level in an experimental set-up. For this purpose, we designed a randomized survey experiment and inquired about preferences on state mergers on a representative sample of the German population. In line with the decentralization theorem, the support for mergers increases with cost savings and falls with preference costs measured as political alignment, respectively. The effects of the cost treatments on merger support are lower for respondents from states that are actually discussed as merger candidates. Effects are also weaker for citizens who have a positive view of their own political participation under the status quo.
Keywords: H11; H77; 330; state-level mergers; optimal design of federations; economies of scale; political representation; survey experiment; decentralization theorem